Women as brand in the Spanish movie posters for the period 2010-2013 - Perales Bazo, Francisco (Historia y Comunicación Social, 2014)
In this work we are going to define and highlight the visual characteristics of women in film poster in recent years (2010-2013) and whether their presence contributes as a brand image for spanish cinematography not only at home but abroad also. Our aim is to establish key visual features on which rests the image transmitted through cinema advertising.